ANALYSIS OF LINGUISTICS INTELLIGENCE ON STUDENTS AT CLASS V SD NEGERI 169 PEKANBARU - Andro, Jefri (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2020)
This research is motivated that there are some abilities that must be present in students namely speaking, reading, writing and listening ability that are closely related to student learning outcomes with indicators like palying words, reading and writing using the word ineffective both verbally and in writing. This study aims to look at the level of linguistic intelligence of elementary school students, consisting of reading, writing, speaking and listening skills. This type of the research was descriptive quantitative research. The population in this study was 175 students. The sample used in this study was a saturated sample. The results of reading skills got an average score of 54.61 with a high enough category while for writing skills got an average score of 54.3 with a fairly high category. Furthermore speaking skills got an average score of 75.06 with a high enough category and for listening skills got an average score of 49.62 with a low category. Then the linguistic intelligence of the fifth grade students of SD Negeri 169 Pekanbaru was classified into a quite high category with an average score of 58.36.